The medicinal chemistry of mitochondrial dysfunction: a critical overview of efforts to modulate mitochondrial health. Issue 8 (4th June 2021) - Lee, Maximillian Taro William; Mahy, William; Rackham, Mark David
Abstract : This manuscript reviews the compounds historically used to modulate mitochondria, and offers a perspective on which targets have been convincingly (in)validated with high quality chemical matter and those which remain untested. Abstract : Mitochondria are subcellular organelles that perform a variety of critical biological functions, including ATP production and acting as hubs of immune and apoptotic signalling. Mitochondrial dysfunction has been extensively linked to the pathology of multiple neurodegenerative disorders, resulting in significant investment from the drug discovery community. Despite extensive efforts, there remains no disease modifying therapies for neurodegenerative disorders. This manuscript aims to review the compounds historically used to modulate the mitochondrial network through the lens of modern medicinal chemistry, and to offer a perspective on the evidence that relevant exposure was achieved in a representative model and that exposure was likely to result in target binding and engagement of pharmacology. We hope this manuscript will aid the community in identifying those targets and mechanisms which have been convincingly (in)validated with high quality chemical matter, and those for which an opportunity exists to explore in greater depth.